Cleavage of Dinitrogen from Forming Gas by a Titanium Molecular System under Ambient Conditions. Issue 15 (20th February 2017) - González‐Moreiras, Mariano; Mena, Miguel; Pérez‐Redondo, Adrián; Yélamos, Carlos
Abstract: Simple exposure of a hexane solution of [TiCp*Me3 ] (Cp*=η 5 ‐C5 Me5 ) to an atmosphere of commercially available and inexpensive forming gas (H2 /N2 mixture, 13.5–16.5 % of H2 ) at room temperature leads to the methylidene–methylidyne–nitrido cube‐type complex [(TiCp*)4 (μ3 ‐CH)(μ3 ‐CH2 )(μ3 ‐N)2 ] via dinitrogen cleavage. This paramagnetic compound reacts with [D1 ]chloroform to give the titanium(IV) methylidyne–nitrido species [(TiCp*)4 (μ3 ‐CH)2 (μ3 ‐N)2 ], whereas its one‐electron oxidation with AgOTf or [Fe(η 5 ‐C5 H5 )2 ](OTf) (OTf=O3 SCF3 ) yields the diamagnetic ionic derivative [(TiCp*)4 (μ3 ‐CH)(μ3 ‐CH2 )(μ3 ‐N)2 ](OTf). The μ3 ‐nitrido ligands of the methylidyne–nitrido cubane complex can be protonated with [LutH](OTf) (Lut=2, 6‐lutidine) or hydrogenated with NH3 ⋅ BH3 to afford μ3 ‐NH imido moieties. Abstract : Made from gas : Commercially available H2 /N2 mixture reacts with a solution of [Ti(η 5 ‐C5 Me5 )Me3 ] in hexane at ambient conditions to give a paramagnetic methylidene–methylidyne–nitrido cube‐type complex by means of dinitrogen cleavage (see scheme).